2004
DOI: 10.1029/2003gc000655
|View full text |Cite
|
Sign up to set email alerts
|

Particles in the great Pinatubo volcanic cloud of June 1991: The role of ice

Abstract: [1] Pinatubo's 15 June 1991 eruption was Earth's largest of the last 25 years, and it formed a substantial volcanic cloud. We present results of analysis of satellite-based infrared remote sensing using Advanced Very High Resolution Radiometer (AVHRR) and TIROS Operational Vertical Sounder/High Resolution Infrared Radiation Sounder/2 (TOVS/HIRS/2) sensors, during the first few days of atmospheric residence of the Pinatubo volcanic cloud, as it drifted from the Philippines toward Africa. An SO 2 -rich upper (25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
120
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(136 citation statements)
references
References 40 publications
14
120
2
Order By: Relevance
“…Lowe et al (1997) suggest that a large effect of enhanced stratosphere-troposphere exchange would be inconsistent with the decrease in observed δ 13 C in this period. However, other isotope data from this period do not support a strong decrease in δ 13 C between 1991(Quay et al, 1999.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Lowe et al (1997) suggest that a large effect of enhanced stratosphere-troposphere exchange would be inconsistent with the decrease in observed δ 13 C in this period. However, other isotope data from this period do not support a strong decrease in δ 13 C between 1991(Quay et al, 1999.…”
Section: Introductionmentioning
confidence: 92%
“…Particles of ash emitted directly by the eruption would also absorb and scatter solar radiation, determining a similar effect on CH 4 lifetime. However, because of their lifetime of only a few days, they are considered to have a negligible global impact (Guo et al, 2004b;Niemeier et al, 2009) and are not included in our study.…”
Section: Introductionmentioning
confidence: 99%
“…Dust emissions are calculated online as a function of wind speed and hydrological parameters according to the Tegen et al (2002) scheme. We do not include volcanic ash emissions as it has been shown that ash sediments within a few days after the eruption from the stratosphere, and the area affected by the ash cloud is relatively small (Guo et al, 2004a). The effect of fine ash on the distribution of the volcanic cloud in the atmosphere is also relatively small .…”
Section: Defining Aerosol Fields With Maecham5-ham-salsamentioning
confidence: 99%
“…Since the flights were carried out in heights below 40 hPa the authors conclude to measure "fallout" from higher elevations. Due to the fact that these spectrometers were calibrated for sulphuric acid only and volcanic ash fallout terminates after a couple days after it was injected into the stratosphere (Guo et al, 2004), it can be assumed that these ultra large particles contain mainly sulphuric acid.…”
Section: Size Distributionsmentioning
confidence: 99%